The role of input and output tasks in grammar instruction: Theoretical, empirical and pedagogical considerations - Benati, Alessandro (Studies in Second Language Learning and Teaching, 2017)
In this paper, a review of the role of input, output and instruction in second language acquisition is provided. Several pedagogical interventions in grammar instruction (e.g., processing instruction, input enhancement, structured output and collaborative output tasks) are presented and their effectiveness reviewed. A final and overall evaluation is provided at the end of the paper.